A Sort of Sepulchral Construction in Wadi Umm Ṭulayḥa, Southeastern Badia, Jordan? - Sadaqah, Ibrahim Saleh; Tarawneh, Mohammad Barakat; Abudanah , Fawzi Qasem (Jordan Journal for History and Archaeology, 2021)
This paper presents a linguistic and etymological analysis of three North Arabian inscriptions carved on a relatively small stone. The stone was found east of al-Jafr in southern Jordan, near the Jordanian-Saudi border. The content of the three inscriptions in terms of writing style, topic, and vocabulary is similar to other North Arabian inscriptions. Nevertheless, the three inscriptions include new words that have not been attested before in other inscriptions of the same type. Some rock drawings were also found in the same rujm.